Co Słychać . związkowy tygodnik NSZZ "Solidarność" Ziemi Ząbkowickiej, no. 38, 1981 - NSZZ "Solidarność" Międzyszkolna Komisja Zakładowa Pracowników Oświaty i Wychowania, ed. Marian Morawski (Międzyzakładowa Komisja Porozumiewawcza NSZZ "Solidarność" Ziemi Ząbkowickiej, 1981)
Creation and circulation: For trade-union use; Place of publiction in print: Ząbkowice Śl.; In 1981 journal published with imprint: Wydawnictwo niezależne i niecenzurowane, pismo jest wolną trybuną dla wszystkich [Independent and uncensored publication, a free tribune for everyone]. After introduction of the Martial Law publication suspended. Republished in 1989. In 1990-1994 published legally